2021
DOI: 10.2196/25131
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Tools to Bridge the Language Gap in Health Care for People Who Have Migrated: Systematic Review

Abstract: Background People who have migrated or with a language barrier may face significant hurdles in accessing health care. Some apps have been specifically developed to facilitate the dialogue between health care professionals and people who have migrated who have low-level language proficiency or to promote health among people who have migrated. Objective We conducted a systematic review to investigate development, acceptability, and effectiveness of these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…82 However, none of these integrate the culturally and linguistically tailored approaches used in in-person studies that have been shown to work in stroke prevention among communities of color and those with limited English proficiency. [83][84][85] Several studies have shown that community health care workers, care navigators, and health educators are important allies in helping patients navigate the complex health care system. A multidisciplinary team including community health care workers, 75 pharmacists, and nurses 86 in the delivery of chronic disease care and cardiovascular health has led to significant improvements in health literacy, risk factor control, self-management behaviors, lifestyle habits, clinical outcomes, and a decrease in inappropriate health care utilization.…”
Section: Secondary Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…82 However, none of these integrate the culturally and linguistically tailored approaches used in in-person studies that have been shown to work in stroke prevention among communities of color and those with limited English proficiency. [83][84][85] Several studies have shown that community health care workers, care navigators, and health educators are important allies in helping patients navigate the complex health care system. A multidisciplinary team including community health care workers, 75 pharmacists, and nurses 86 in the delivery of chronic disease care and cardiovascular health has led to significant improvements in health literacy, risk factor control, self-management behaviors, lifestyle habits, clinical outcomes, and a decrease in inappropriate health care utilization.…”
Section: Secondary Preventionmentioning
confidence: 99%
“…82 However, none of these integrate the culturally and linguistically tailored approaches used in in-person studies that have been shown to work in stroke prevention among communities of color and those with limited English proficiency. 83–85…”
Section: Secondary Preventionmentioning
confidence: 99%
“…Prior to the COVID-19 pandemic strategies beyond language interpretation to support patients with LEP have included specific clinic days with language-congruent clinicians [46], huddles between clinicians and interpreters [47], continuing education sessions on caring for patients with LEP [48], electronic apps for health promotion and communication providers [49], and chronic disease education via group video visits by community health workers [50]. Most interventions described in the literature occur in non-hospitalized patients, such those seen in outpatient clinics or through community outreach [46,49,51]. However, these strategies may not be applicable when caring for individual patients in higher-acuity settings, such as those who are hospitalized or in ICU.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review Investigating the use of electronic tools to help increase testing in migrants with LFP, conducted by our research team, found that translation apps provide better communication with HPs and have a high acceptability of use [ 10 ]. In terms of a new tool, our research found that HPs spoke most frequently of an easy to use ( Figure 1 , subtheme 3.2), accessible app with multiple features, including visual ( Figure 1 , subthemes 4.1-4.2) and audio ( Figure 1 , subtheme 4.3) components along with an accurate, reliable, and instantaneous translation ( Figure 1 , subtheme 3.1); data collection; adaptive content; and interpretation functions ( Figure 1 , subthemes 5.1, 5.2, 5.3, and 5.4).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review investigating language barriers in migrant health care found that translation apps enable better communication in the patient-provider relationship and reduce overall consultation times [ 10 ]. Another study demonstrated that a mobile translation app contributed to the use of interpretation services and resulted in a high level of satisfaction among HPs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%